Climate Injustice: The legal analysis of the Human Rights Impact in Pakistan and Lessons from Germany - Dr. Asma Mehboob; Maheen Yasin Mirza; Iram Farid (Social Science Review Archives, 2025)
The study explores the unmitigated impacts of climate change on human rights in Pakistan, highlighting the need for rights-based climate governance. It highlights the potential to undermine key human rights, such as life, health, water, food, and shelter, particularly for Pakistan's vulnerable populations. Despite the country's protections under the constitution and domestic legislation, such as the Pakistan Climate Change Act 2017, the state response is reactive, ineffective, and weakly enforced. Pakistan is a party to international agreements like the United Nations Framework Convention on Climate Change (UNFCCC), Paris Agreement, and human rights treaties, but there are gaps in protection between these commitments and domestic implementation. The study further compares Germany’s approach which has increasingly come to term climate action as a human rights obligation with powerful legal mechanisms, environmental litigation, and conformity to international climate conventions and directives. The experience of Germany with the international environmental model shows that how a nation can incorporate international obligations into its domestic legal systems that can contribute to the protection of country’s environment as well as its human rights. The policy recommendations that follow from this comparison include integrating international standards into legally binding local legislation, enhancing the ability of institutional stakeholders, and for the first time recognizing the impact of change as a human rights concern. The conclusion of the study is that bridging the gap between Pakistan’s international climate and human rights obligations and national legal framework is a prerequisite for climate justice and protecting the dignity of the present and the future generations.